Chaos in a hybrid food chain model - Jawad Ali, Safaa; Naji Almohasin, Abed Almohsen; Naji, Adwea Atewi; Naji, Raid Kamel; Md Arifin, Norihan (Baghdad University, 2021)
In this paper, chaotic and periodic dynamics in a hybrid food chain system with Holling type IV and Lotka-Volterra responses are discussed. The system is observed to be dissipative. The global stability of the equilibrium points is analyzed using Routh-Hurwitz criterion and Lyapunov direct method. Chaos phenomena is characterized by attractors and bifurcation diagram. The effect of the controlling parameter of the model is investigated theoretically and numerically.